2016
DOI: 10.1016/j.archger.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of dementia: Systematic review and meta-analysis of hospital administrative database studies

Abstract: Compared to older adult population, patients with dementia had poorer outcome. Despite higher mortality rate and readmission rate, they underwent fewer interventions and procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 30 publications
6
58
0
3
Order By: Relevance
“…A recently published meta-analysis investigating mortality in mental disorders including 43 studies of depression showed that the mortality was almost two times higher in people with depression as compared to the general population [13]. Similarly, dementia has been associated with increased mortality from another meta-analysis [16]. …”
Section: Introductionmentioning
confidence: 99%
“…A recently published meta-analysis investigating mortality in mental disorders including 43 studies of depression showed that the mortality was almost two times higher in people with depression as compared to the general population [13]. Similarly, dementia has been associated with increased mortality from another meta-analysis [16]. …”
Section: Introductionmentioning
confidence: 99%
“…However, there was no analysis of the impact of CI on postoperative outcomes. Similarly, a review by Rao et al examined the outcomes of patients with dementia versus patients without dementia [38]. However, that study focused on patients with diagnosed dementia, as opposed to cognitive impairment, which is both more prevalent and less clinically apparent.…”
Section: Tablementioning
confidence: 99%
“…Obwohl Patienten mit Demenz je Aufenthalt einen vergleichbaren Charlson-Komorbiditäts-Score und eine ähnliche Verweildauer aufwiesen, erhielten sie je Krankenhausaufenthalt weniger diagnostische und therapeutische Leistungen als die Vergleichsgruppe. DiesdecktsichmitResultatenvergleichbarerStudien [22].Häufigerwarenhingegendie"ErgänzendenLeistungen".Darunterfallenbspw.aufwendigePflegemaßnahmen(▶ Tab. 5)oderdieBehandlung von behavioralen und psychischen Symptomen.…”
Section: Akutstationäre Versorgungunclassified
“…5)oderdieBehandlung von behavioralen und psychischen Symptomen. Die Gründe für eine geringere Inanspruchnahme sind multifaktoriell: Erstens ist denkbar, dass bei (fortgeschrittener) Demenz eher auf Maßnahmen verzichtet wird, da man sich von ihnen möglicherweise keine Verbesserungen des Gesundheitszustandes erwartet [22]. ZweitenskönntenMaßnahmenunterlassenwerden,dadashäufigere Auftreten von behavorialen und psyschischen Symptomen oder Delirien bei Patienten mit Demenz die Durchführung von diagnostischen und therapeutischen Maßnahmen erschweren, aufwendig oder unmöglich machen.…”
Section: Akutstationäre Versorgungunclassified